2017
DOI: 10.1155/2017/1943432
|View full text |Cite
|
Sign up to set email alerts
|

Porous Cellulose Beads Fabricated from Regenerated Cellulose as Potential Drug Delivery Carriers

Abstract: Highly porous cellulose beads (CBs) of various mean sizes were successfully prepared from regenerated cellulose of paper wastes. The drug delivery characteristics of CBs with different mean sizes were investigated using curcumin as the model drug under controlled conditions. The loading capacity and efficiency of curcumin onto CBs were substantially influenced by factors such as their morphological characteristics, curcumin concentration, and duration of loading. The release kinetic profiles of curcumin from C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…1-allyl-3-methylimidazolium chloride, an ionic liquid was used as solvent to prepare cellulose particles from cellulose paper wastes [173]. Using a syringe, the cellulose solution was dropped into a water coagulation medium.…”
Section: State Of the Art Of Bio-aerogel Particlesmentioning
confidence: 99%
“…1-allyl-3-methylimidazolium chloride, an ionic liquid was used as solvent to prepare cellulose particles from cellulose paper wastes [173]. Using a syringe, the cellulose solution was dropped into a water coagulation medium.…”
Section: State Of the Art Of Bio-aerogel Particlesmentioning
confidence: 99%
“…Cellulose beads (CBs) are smaller-sized particles prepared through the usual route of dissolution of cellulose or cellulose derivatives followed by shaping into a spherical form, sol–gel transition, drying, and fine-tuning of pore characteristics [ 137 ]. Particularly, shaping is the most crucial step in CBs preparation, which is usually achieved either by dispersion techniques or dropping the cellulose solution into a coagulating bath using droplet forming machines such as atomizers and jet cutting machines [ 138 ]. In the dropping technique, beads are formed by the solidification of cellulose solution by adding it drop-wise into an aqueous coagulating medium ( Figure 6 ).…”
Section: Surface Modification Of Cellulose and Cellulose Bioproductsmentioning
confidence: 99%
“…Curcumin release study was conducted based on the methodology reported by Voon et al 7,19 About 50 mg of curcumin loaded amino-starch nanoparticles were dispersed in 15 ml of phosphate-buffered saline (PBS) at two different pH values:…”
Section: Curcumin Release Studymentioning
confidence: 99%